STRATEGIES FOR IMPROVING SUPPLY CHAIN PERFORMANCE OF KAYUMAS SPECIALTY COFFEE - Risanda, Aisya; Muhaimin, Abdul Wahib; Maulidah, Silvana (Socio-Economics/Agribusiness Department, 2024)
Performance evaluation is essential in defining supply chain strategies because by taking measurements, companies can find out how the business processes in the supply chain are running and formulate strategic policies to improve supply chain performance. Specialty coffee is a premium coffee with a unique aroma and flavor originating from a specific region, and it is easy to trace its origin from the farm to the consumer. This study aims to evaluate the performance of the Kayumas specialty coffee supply chain using the SCOR-ANP method and determine performance improvement strategies using ANP analysis. The research results can be concluded that (1) Kayumas specialty coffee supply chain consists of farmers, farmer groups, distributors/resellers, and consumers, (2) the performance position of Kayumas specialty coffee is inferior, (3) the performance improvement strategy needed to improve product quality is a partnership between supply chain members to reach a price agreement.